EXAMINE THE EFFECTS OF GOODS AND SERVICES TAX (GST) AND ITS COMPLIANCE: REFERENCE TO SIERRA LEONE : Received: 29th November 2023; Revised: 21st December 2023; Accepted: 22nd December 2023 - Kaira, Lamin; Conteh, Abdul; Hamza Conteh, Alhaji Mohamed (PEOPLE: International Journal of Social Sciences, 2024)
This study analyzes the effects of (GST) and how it is being implemented in Sierra Leone. GST replaces previous taxes, including domestic sales tax, import sales tax, entertainment tax, hotel room tax, restaurant tax, food tax etc. The objectives of this study are to know the effect of GST on the Sierra Leone Economy, to know if GST implementation will lead to an increase in prices of goods and services; to assess GST compliance rate in Sierra Leone; and to know the reasons for GST implementation in Sierra Leone. The data collection method used both primary and secondary sources the study’s participants were 89 employees of NRA and business owners in Sierra Leone 2021 to 2023. Questions were analyzed using SPSS in the form of descriptive analysis, chart, and correlation coefficient. The results showed that GST implementation has positive effects on Sierra Leone Economy. The introduction of GST is to boost revenue and promote economic growth in Sierra Leone. GST introduction in Sierra Leone has resulted in increased prices of goods and services. It is recommended that the NRA should provide tax education and awareness and provide availability and accessibility of technological infrastructure for GST implementation in the country.